Pengaruh Penambahan Abu Batu (Fly Ash) Terhadap Plastisitas Tanah Lempung Di Kabupaten Fakfak - Muhammad Yunus; Muhammad Aswan (Politeknik Negeri Jakarta, 2020)
The road conditions in the Fakfak Regency area have suffered a lot of damage, this is related to the subgrade condition of the road in the form of clay. One method that is widely used to improve the characteristics of clay that does not fulfill the requirements as a road subgrade material is to add fly ash. Aim of this study was to determine the value of clay plasticity before and after adding rock ash with the percentage of stone ash 8%, 16%, 32%. From the results of testing on clay soaked for 7 days can reduce the liquid limit value where the largest decrease is 15,24% of the original soil occurs in the addition of 32% fly ash with a value of 66,86%. The plastic limit value also decreased by 20,40% from the original soil with a value of 46,10% at the addition of 32% fly ash. And the plasticity index value experienced the largest decrease in the addition of 32% stone ash with a decrease of 0,97% from the original soil with a value of 20,76%. In clay soil which was brooded for 14 days the largest liquid limit value decreased which was 18.72% of the original soil occurred in the addition of 32% fly ash with a value of 64,11%. The plastic limit value also decreased by 21,77% from the original land with a value of 45,31% at the addition of 32% fly ash. And the plasticity index value experienced the largest decrease in the addition of 32% stone ash with a decrease of 10,32% from the original land with a value of 18,80%.